Elevating Students’ Narrative Writing Ability Through Local Legend Picture Series - Syailendra, Axel; Karim, Sayit Abdul; Matas, Gordan; Ramli, Ramli; Ismail, Hijril (Universitas Pendidikan Mandalika, 2024)
This research aimed to detect students' ability to write narrative text using local legendary picture series and further explore their perceptions of using picture series in writing narratives. A descriptive quantitative research design was employed, and 30 students (10 males and 20 females) participated as respondents in the present study. Furthermore, the students were asked to write a narrative text based on a series of pictures from the local legend of Danau Toba. The findings indicated that picture series significantly enhanced students' narrative writing skills. The average scores revealed that the organization, vocabulary, and grammar were 3.19, 3.43, and 2.92 respectively, categorized into the